Popularitas Politikus: Antara Kerja Politik atau Kehebatan Televisi - Rahmat Edi Irawan (Humaniora, 2014)
Popularity is coveted by politicians before general election. Politicians who have high popularity have a much larger capital to be successfully elected in general election. In contrast, ordinary or even low popularity will be difficult for politicians to win public institution seats contested. The problem is about how to increase the popularity for politicians. This paper discusses about relationship between the popularity of politicians with political work and the greatness of television, whether it is true that the increase in popularity of politicians can only be done with political work, or in the contrary, the increase in the popularity of politicians can be done with the use of television media, as the media are most widely used in the community. Discussion of this paper was done using literature study obtained from political communication and mass communication books related to this matter. In addition, data from recent news media, especially regarding the popularity of the politicians, political work and the use of television media in general elections were also used to enrich this paper. Result of this literature study concludes that popularity of the politicians has become a major requirement for politicians to succeed in general election. Popularity of the politicians is synonymous with political work. Political work done continuously in approaching the constituent is the way to boost the popularity. Nevertheless, the political work is not enough. Currently, efforts to boost popularity needs mass media, especially television, which can introduce politicians to their constituents who are also the television audience.